Perioperative morbidity and mortality in dogs with invasive adrenal neoplasms treated by adrenalectomy and cavotomy. Issue 5 (29th April 2019) - Mayhew, Philipp D.; Boston, Sarah E.; Zwingenberger, Allison L.; Giuffrida, Michelle A.; Runge, Jeffrey J.; Holt, David E.; Raleigh, Joseph S.; Singh, Ameet; Culp, William T. N.; Case, J. Brad; Steffey, Michele A.; Balsa, Ingrid M.
Abstract: Objective: To report the morbidity and mortality associated with adrenalectomy with cavotomy for resection of invasive adrenal neoplasms in dogs and evaluate risk factors for perioperative outcomes. Study design: Retrospective study. Animals: Forty‐five client‐owned dogs. Methods: Dogs that underwent open adrenalectomy with cavotomy for resection of adrenal masses with tumor thrombus extending into the vena cava were included. Clinicopathologic data were harvested from medical records. Selected clinical, imaging, and operative variables were statistically evaluated as risk factors for packed red blood cell transfusion, nephrectomy, perioperative death, and overall survival. Results: Thirty‐six of 45 masses were pheochromocytomas, 7 were adrenocortical carcinomas, and 2 were unknown type. Caval thrombus terminated prehepatically in 21 of 45 dogs and extended beyond the porta hepatis but terminated prediaphragmatically (intrahepatic prediaphragmatic location) in 15 dogs and thrombi extended postdiaphragmatically in 5 dogs. Thirty‐four (76%) dogs were discharged from the hospital, and 11 (24%) dogs died or were euthanized prior to discharge. Median overall survival time for all 45 dogs was 547 days (95%CI 146–710). Bodyweight, tumor type, and size and extent of caval thrombus did not affect survival to discharge, but postdiaphragmatic (rather than prediaphragmatic) thrombus termination was associated with a greater risk of death. Conclusion: Long‐term survival was common in dogs that survived the perioperative period. Postdiaphragmatic thrombus extension affected the prognosis for overall survival. Clinical significance: Findings of this study help to stratify operative risk in dogs with adrenal neoplasia and caval invasion.